Floristic and dispersion syndromes of Cerrado species in the Chapada do Araripe, Northeast of Brazil (Research, Society and Development, 2020)
Through this study, the objective was to contribute to the knowledge regarding floristic composition, classification and conservation status of the studied plant species as well as the dispersion syndromes of flora found in a disjoint Cerrado area ​in the Chapada do Araripe, Crato-CE. For the research development Rapid Survey method, applied in three walking lines (Line 1, Line 2 and Line 3) was adopted. Floriferous branches, fruits and seeds from species in the study area were collected in order to identify them and to characterize their diaspores, in view of fitting them into the corresponding dispersion syndromes. A total of 103 species were identified, the richest species taxa were: Fabaceae, Apocynaceae, Euphorbiaceae, Malpighiaceae and Myrtaceae. The most abundant species in the studied area were: Cordiera myrciifolia (“bola”) Miconia albicans (“Candeiro-de-pelo”), Caryocar coriaceum (pequi) and Copaifera langsdorffii (“pau d'oleo”). Three new occurrences were also recorded for the state of Ceará: Eriope tumidicaulis, Myrciaria cf. tenella and Stachytapheta cf. crassifolia. The most frequent dispersion syndrome was zoochoria, followed by anemocoria. Considering that most of the species occurring in the study area have their dispersion diaspores transported by a fauna element, the importance of these species for the maintenance of the observed floristic richness is evident.